Aset Tetap : Pengakuan, Pengukuran, Penyajian dan Pengungkapan - Eka Setiajatnika; Trida Gunadi; Nuri Nurhayati; Dady Nurpadi (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Recognition, Measurement, Presentation and Disclosure of Fixed Assets. This research was conducted at the Wredatama Sumedang City Cooperative which is one of the cooperatives in the Sumedang Regency which is engaged in the savings and loan sector. The purpose of this study was to determine the recognition, measurement, presentation and disclosure of fixed assets in the Wredatama Sumedang City Cooperative. In this study the authors used quantitative methods. Analysis of the data used is descriptive analysis. The data collection techniques carried out were interviews and questionnaires to the Management of the Wredatama Sumedang City Cooperative, observations of fixed assets and documentation of fixed asset.The results showed that the recognition of fixed assets was in accordance with SAK ETAP (Entity Financial Accounting Standards Without Public Accountability). The measurement of fixed assets is not in accordance with SAK ETAP due to an error in calculating the value of accumulated depreciation and no depreciation is carried out for 3 (three) years, in the presentation of fixed assets the accumulated depreciation account is not presented as a deduction from fixed assets and the nominal depreciation presented on the statement of financial position is not in accordance with carrying amount in the detailed list of fixed assets and last on the disclosure not disclosed regarding the depreciation method used and there is no provision for the useful life of fixed assets.